Chi ha (i)scritto il film? Di orsi, naturalisti e cineasti - Michele Guerra (Rivista di Estetica, 2012)
The film, as the term itself implies, entails a recording and a particular kind of writing. Nonetheless, this is not enough to consider it as a social object. It needs a formal and narrative structure and, above all, it needs an inscription in order to give it a sociality based upon its diffusion. The amateur movies represent a perfect example of this condition: they are often recordings without any inscription and remain within a very narrow communicative circle. They certainly document something, but they do not have the form of a social object. Grizzly Man (Werner Herzog, 2005) is a movie by a director who did not shoot the most impressive scenes of it. Is Herzog an impostor? Certainly not. He is simply the man who gave an inscription to the amateur movies he found, transforming them into social objects.